Synaptic oligomeric Tau is an early event in tau‐affected brain regions in Alzheimer's disease. (20th December 2022) - Dolcet, Sònia Sirisi; Colom‐Cadena, Martí; Querol‐Vilaseca, Marta; Rose, Jamie; Sánchez‐Aced, Érika; Andrian, Teodora; Pujals, Sílvia; Horrocks, Mathew; Lleó, Alberto; Spires‐Jones, Tara L
Abstract: Background: Deposition of fibrillar forms of tau‐neurofibrillary tangles (NFT) and neuropil threads (NT) follow a progressive pattern across brain regions as reflected by Braak stages. However, oligomeric forms of tau have been proposed to precede the appearance of fibrillar forms. Synapses are the earliest structure linked to Azheimer's Disease cognitive loss, but whether tau pathology, fibrillar or oligomeric affects early this structure in each region remains unclear. This is mainly explained by the technical limitations to study oligomeric forms of tau and the visualization of synaptic terminals. We aim to investigate the presence of oligomeric tau at synapses of human AD cases and its relation to the presence of fibrillar forms of tau in different brain regions. Method: We used array tomography microscopy to visualize single synaptic terminals on postmortem human samples from BA20/21 and BA17 brain regions of 10 AD and 10 controls with diverse Braak stages. Pre‐ and post‐synaptic terminals (synaptophysin and PSD95) and oligomeric tau (T22 antibody) were labelled. To compare synaptic tau with total fibrillar tau burden, NFTs and NTs were quantified from immunohistochemical sections (AT8 antibody) of the same cases and areas. We also studied the presence of tau in synapses using Western Blot experiments in synaptoneurosomes enriched fractions from the same cases and areas (Tau5 antibody). Finally, the presence at synapses of oligomeric and fibrillar tau was confirmed with other superresolution techniques such as electron microscopy, STORM and DNA‐PAINT. Result: We found that 1) Oligomeric tau was found in both pre‐ and postsynaptic terminals, in a higher proportion of presynaptic terminals. 2) Oligomeric tau at synapses was found in areas without abundant fibrillar forms of tau. 3) A higher proportion of oligomeric tau when compared to phosphorylated tau was found at synaptic terminals in early affected cases. 4) Early synaptic oligomeric tau was found also by western blot of synaptoneurosomes, electron microscopy and STORM. Conclusion: Our results suggest that synaptic oligomeric tau may be an early event at tau‐affected brain regions, preceding the phosphorylation of tau and the formation of fibrillar forms. Also, the findings may support the transsynaptic spreading of tau at early stages.